Acidic tumor microenvironment abrogates the efficacy of mTORC1 inhibitors. Issue 1 (December 2016) - Faes, Seraina; Duval, Adrian; Planche, Anne; Uldry, Emilie; Santoro, Tania; Pythoud, Catherine; Stehle, Jean-Christophe; Horlbeck, Janine; Letovanec, Igor; Riggi, Nicolo; Demartines, Nicolas; Dormond, Olivier
Abstract Background Blocking the mechanistic target of rapamycin complex-1 (mTORC1) with chemical inhibitors such as rapamycin has shown limited clinical efficacy in cancer. The tumor microenvironment is characterized by an acidic pH which interferes with cancer therapies. The consequences of acidity on the anti-cancer efficacy of mTORC1 inhibitors have not been characterized and are thus the focus of our study. Methods Cancer cell lines were treated with rapamycin in acidic or physiological conditions and cell proliferation was investigated. The effect of acidity on mTORC1 activity was determined by Western blot. The anticancer efficacy of rapamycin in combination with sodium bicarbonate to increase the intratumoral pH was tested in two different mouse models and compared to rapamycin treatment alone. Histological analysis was performed on tumor samples to evaluate proliferation, apoptosis and necrosis. Results Exposing cancer cells to acidic pH in vitro significantly reduced the anti-proliferative effect of rapamycin. At the molecular level, acidity significantly decreased mTORC1 activity, suggesting that cancer cell proliferation is independent of mTORC1 in acidic conditions. In contrast, the activation of mitogen-activated protein kinase (MAPK) or AKT were not affected by acidity, and blocking MAPK or AKT with a chemical inhibitor maintained an anti-proliferative effect at low pH. In tumor mouse models, the use of sodium bicarbonate increased mTORC1 activity in cancer cells and potentiated the anti-cancer efficacy of rapamycin. Combining sodium bicarbonate with rapamycin resulted in increased tumor necrosis, increased cancer cell apoptosis and decreased cancer cell proliferation as compared to single treatment. Conclusions Taken together, these results emphasize the inefficacy of mTORC1 inhibitors in acidic conditions. They further highlight the potential of combining sodium bicarbonate with mTORC1 inhibitors to improve their anti-tumoral efficacy.